A rare case report of bilateral ruptured tubal ectopic pregnancy - Preeti Shankar Malapure; Rajasri G Yaliwal; Purushottam B Jaju; Gauri Bankapur (Wolters Kluwer Medknow Publications, 2022)
Implantation of the fertilized ovum outside the uterine cavity is called ectopic gestation. The common presenting symptoms are per vaginal bleeding till 12 weeks, pain in the lower abdomen, and absence of menses. ß-HCG level is increased (>1000IU/L) and transvaginal ultrasonography shows an empty uterus. These findings essentially confirm the diagnosis. In this, we have a 23-year-old, G2P1L1 with a history of 3 months of amenorrhea, presenting to the labor ward with a history of per vaginal bleeding and lower abdominal pain. The diagnosis was 10 weeks right-sided ruptured ectopic pregnancy and intraoperatively found to be ruptured ectopic pregnancy in both fallopian tubes which we managed successfully by performing emergency laparotomy with bilateral partial salpingectomy.